2016
DOI: 10.3389/fpls.2016.01550
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Barley Calcium-Dependent Protein Kinase CPK2a in the Response to Drought

Abstract: Increasing the drought tolerance of crops is one of the most challenging goals in plant breeding. To improve crop productivity during periods of water deficit, it is essential to understand the complex regulatory pathways that adapt plant metabolism to environmental conditions. Among various plant hormones and second messengers, calcium ions are known to be involved in drought stress perception and signaling. Plants have developed specific calcium-dependent protein kinases that convert calcium signals into pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…When barley and rice roots were colonized by endophytic basidiomycete fungi (P. indica), the host plants enhanced performance under salinity stress (Baltruschat et al, 2008;Vahabi et al, 2016;Jogawat et al, 2016). The protein kinase superfamily is another important gene family that has been characterized in several plants; e.g., for drought tolerance in barley (Cieśla et al, 2016;Yang et al, 2017) and salinity stress tolerance in wheatgrass (Shen et al, 2001). Protein kinase gene family, regulated by transcription factors (TFs) and microRNAs (miRNAs), plays key roles in salt stress tolerance in cotton (Shehzad et al, 2019).…”
Section: Candidate Genes Reveal the Possible Molecular Basis Of Salinmentioning
confidence: 99%
“…When barley and rice roots were colonized by endophytic basidiomycete fungi (P. indica), the host plants enhanced performance under salinity stress (Baltruschat et al, 2008;Vahabi et al, 2016;Jogawat et al, 2016). The protein kinase superfamily is another important gene family that has been characterized in several plants; e.g., for drought tolerance in barley (Cieśla et al, 2016;Yang et al, 2017) and salinity stress tolerance in wheatgrass (Shen et al, 2001). Protein kinase gene family, regulated by transcription factors (TFs) and microRNAs (miRNAs), plays key roles in salt stress tolerance in cotton (Shehzad et al, 2019).…”
Section: Candidate Genes Reveal the Possible Molecular Basis Of Salinmentioning
confidence: 99%
“…A positive regulatory effect of CDPKs in drought stress signaling was explained by the improved expression of ABA-responsive genes [72]. Ciesla et al [73] reported that the gene encoding the calciumdependent protein kinase HvCPK2a was significantly upregulated in barley (Hordeum vulgare L.) in response to drought. The CBL-interacting protein kinase 16 gene was differentially expressed in three barley genotypes throughout the reproductive stage under drought stress [74].…”
Section: Discussionmentioning
confidence: 99%
“…ABA is the most critical phytohormone in plant drought stress responses, and several plant CPKs are involved in the mechanisms of drought stress response through an ABA-dependent manner [43]. The Arabidopsis plants overexpressing VaCPK20 gene showed increased drought tolerance, and enhanced the transcripts of COR47, NHX1, KIN1, and ABF3 genes, which were induced by ABA and drought stresses [44].…”
Section: Tacpk34 Could Regulate Expression Of the Target Genes In Resmentioning
confidence: 99%